Damage Analysis of Surface Layer on Jl. Pemuda, Sungai Rengas Using Pavement Condition Index (PCI) And Bina Marga Method - Saraswati, Tiara; Mayuni, Siti; Mukti, Elsa Tri (Fakultas Teknik Universitas Tanjungpura, 2024)
Road damage will have a detrimental impact, disrupting economic and social activities and causing high accident rates. Road damage is the decline in road quality caused by many factors, both in function and structural damage. This study analyzes road damage conditions to identify the types, levels, and solutions for addressing road damage using the Pavement Condition Index (PCI) and the Bina Marga Method on Jl. Pemuda, Sungai Rengas, Kubu Raya Regency. The PCI analysis found four types of damage on Jl. Pemuda: bleeding, edge cracking, potholes, and raveling. The road condition value shows that the Jl. Pemuda section is in the Very Poor category with a condition value of 21,80, and the handling solution is reconstructed according to the Asphalt Institute MS - 17 method. The analysis results using the Bina Marga method found four types of damage on Jl. Pemuda: pothole, raveling, fatty, and edge cracking. The road condition value was found to be a priority order with a value of 6, which means it falls into the category of a periodic maintenance program, which is also a handling solution coupled with several Standard Bina Marga 2011 methods